إظهار أثر العقيدة الإسلامية على الاضطرابات النفسية: دراسة ميدانية محافظة أربيل أنموذجا - طاهر، طاهر محمد; إسماعيل، أردوان مصطفي (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2023)
تهدف هذه الدراسة إلى إظهار أثر العقيدة الإسلامية لمعالجة الأمراض النفسية، وأثرها على وقاية الإنسان من تلك الأمراض، ولتحقيق ذلك تم أخذ عينة عشوائية من ثلاث مجموعات من محافظة أربيل، المجموعة الأولى: مجموعة من الأطباء النفسيين من مستشفى أربيل النفسي وعددهم (۲۲) طبيبا. المجموعة الثانية: مجموعة من مرضى النفسيين من مستشفى أربيل النفسي تم اختيارهم عشوائيا وعددهم (۲۳) مريضا. المجموعة الثالثة: اختيار عينة عشوائية من غير الأطباء والمرضى النفسيين من أفراد محافظة وعددهم (٦٦٠) شخصا. وكأداة لجمع بيانات الدراسة اعتمدت الدراسة على توزيع الاستبيان على المجموعات الثلاث من مركز محافظة أربيل وإدارة سوران المستقلة وستة من أقضيتها وثمانية من نواحيها، كما اقتضت فرضيات الدراسة أن تكون الاستبيان في ثلاث صور مختلفة لكل مجموعة استبيان خاص به. واعتمدت الدراسة على المنهج الوصفي التحليلي، وكان من أهم نتائج الدراسة قوة أثر العقيدة الإسلامية على الأمراض النفسية وقاية وعلاجا وتخفيفا، وكذلك وقاية العقيدة والتدين للمرء بصورة جيدة من الإصابة بالأمراض النفسية، إظهار أثر إيجابي للدين والتدين لمعالجة الأمراض النفسية، كما توصلت الدراسة إلى أن الغالبية العظمى من المرضى والمتمتعين بالصحة النفسية في العينة يشعرون بالسعادة والاطمئنان عند ممارسة العبادات والواجبات. ثم ختمت الدراسة بمجموعة النتائج والاقتراحات والتوصيات. The most important of this study is to clarify the Islamic belief in treating mental illnesses, and its impact on human protection from these diseases, and the fact that a technique was taken from three groups from Erbil Governorate, the first group: a group of psychological indicators from Erbil Psychiatric Hospital, numbering (22) doctors. The second group: a group of ill patients from Erbil Psychiatric Hospital, who were selected indirectly, numbering (23) patients. The third group: Selection of unspecified personalities and mental patients from the members of the district, numbering (660) people. As a tool for collecting data for the study, the study relied on distributing the questionnaire to the three groups in the center of Erbil, the Autonomous Administration of Soran, six of its districts, and eight of its sub-districts. The study relied on the analytical descriptive model, and one of the most important results of the study was the power of the Islamic faith on mental illness, its treatment and mitigation. They agree, to some extent, that religion and religiosity have a positive contribution to eating nutritional diseases. The study also found that patients and healthy meditation in the sample increased their sense of happiness when practicing acts of worship and duties. Then the study concluded with a set of suggestions and recommendations and the most important results.
Keywords: الشريعة الإسلامية -- المشاكل النفسية -- العلاج النفسي